Remote ischemic conditioning (RIC) with exercise (RICE) is safe and feasible for acute ischemic stroke (AIS) patients - Tong, Yanna; Lee, Hangil; Kohls, Wesley; Han, Zhenzhen; Duan, Honglian; Cheng, Zhe; Li, Fenghai; Gao, Jie; Liu, Jing; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2022)
Objective: Rehabilitation is essential in reducing stroke disability and should be performed as early as possible. Exercise is an established and effective rehabilitation method; however, its implementation has been limited as its very early use exacerbates cerebral injury and is restricted by patients’ unstable conditions and disabilities. Remote ischemic conditioning (RIC) is a passive and accessible therapy in acute phases of stroke and appears to have similar neuroprotective effects as exercise. This study assessed the safety and feasibility of the novel rehabilitation strategy—early RIC followed by exercise (RICE) in acute ischemic stroke (AIS). Methods: We conducted a single-center, double-blinded, randomized controlled trial with AIS patients within 24 hours of stroke onset or symptom exacerbation. All enrolled patients were randomly assigned, at a ratio of 1:1, to either the RICE group or the sham-RICE group (sham RIC with exercise). Each group received either RIC or sham RIC within 24 hours after stroke onset or symptom exacerbation, once a day, for 14 days. Both groups started the exercise routine on day 4, twice daily, for 11 total days. The safety endpoints included clinical deterioration, recurrence of stroke, hemorrhagic transformation, complications, and adverse events resulting from RICE during hospitalization. The efficacy endpoints [Modified Rankin Scale (mRS) score, National Institutes of Health Stroke Scale (NIHSS) score, Barthel Index, and walking ability] were evaluated at admission and 90 days after stroke onset. Results: Forty AIS patients were recruited and completed the study. No significant differences in baseline characteristics were found between the two groups, which included risk factors, stroke severity at admission, pre-morbid disability, and other special treatments. No significant differences were found in the safety endpoints between two groups. Excellent recovery (mRS 0–2) at 3 months was obtained in 55% of the patients with RICE as compared 40% in sham group, but it did not reach a significant level. Conclusions: RICE was safe and feasible for AIS patients, and seems to be a promising early stroke rehabilitation. The results of this study suggest a need for a future randomized and controlled multicenter trial with a larger sample size to determine the efficacy of RICE.